2017
DOI: 10.1177/1037969x17732705
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking resettlement and family reunion in Australia

Abstract: Family reunion remains a significant issue for refugee communities in Australia. Family separation causes significant psychological, social and economic harm to displaced communities. Instead of supporting the reunion of refugee families, the current law and policies make it increasingly difficult, if not impossible, for refugees to bring their family members to Australia. This article outlines the barriers to family reunion for refugees under Australian law and policy and addresses how such policies could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 0 publications
0
16
0
4
Order By: Relevance
“…Several studies have shown that an insecure visa status is associated with poorer mental health and psychosocial adjustment in the resettlement environment [32,65,66]. One possible explanation for this is that those with insecure visas may be more likely to experience family separation (in Australia [67]). Thus, it may be challenging for insecure visa holders to seek support from social and community sources when their social network is greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that an insecure visa status is associated with poorer mental health and psychosocial adjustment in the resettlement environment [32,65,66]. One possible explanation for this is that those with insecure visas may be more likely to experience family separation (in Australia [67]). Thus, it may be challenging for insecure visa holders to seek support from social and community sources when their social network is greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of forced displacement, family separation often occurs through the confused process of fleeing active conflict or leaving family members behind to seek asylum in the hope of eventual reunification (Oxfam and Refugee Council UK, 2018). Simultaneously, there is a global trend towards tougher policies around family reunification allowances for those seeking asylum in order to deter migrants and secure borders (Okhovat et al, 2017). Consequently, long-term family separation is a reality for many refugees.…”
mentioning
confidence: 99%
“…without a valid visa) currently have little chance for family reunification as they are either unable to sponsor family members to migrate to Australia or are blocked from travelling overseas without Government permission. Even with permanent residency, refugees frequently wait for years to be physically reunited with family members, with barriers including limited intakes, restricted definitions of ‘immediate family’ and prohibitive application costs (Okhovat et al, 2017). Australian policies are reflective of those now implemented in other countries, including the United Kingdom (Oxfam and Refugee Council UK, 2018).…”
mentioning
confidence: 99%
“…A legislação da África do Sul garante uma definição expandida de família que inclui esposos, qualquer filho solteiro dependente ou qualquer membro da família do refugiado ou do solicitante de refúgio que seja destituído, idoso ou enfermo (KHAN, 2013). Já a definição de família na Austrália é a de "membros da família imediata", ou seja, esposos ou companheiro de fato, crianças dependentes e pais no caso de requerentes menores de 18 anos (OKHOVAT et al, 2017).…”
Section: Discussões Sobre Família E Dependênciaunclassified
“…Isso faz com que refugiados tenham que esperar longos anos antes de serem reunidos com seus familiares. Outro problema é que as famílias refugiadas têm que demonstrar a dependência antes de aplicar para a reunião familiar(OKHOVAT et al, 2017), o que nem sempre é fácil, considerando a ausência de documentação e o fato de que muitos refugiados não estão completamente inseridos no mercado de trabalho australiano.Outro impeditivo da reunião familiar na Austrália são os custos envolvidos no processo, de bilhetes aéreos, agentes de migração, taxas legais e apoio ao reassentamento. Além disso, aqueles que chegaram à Austrália de barco sem um visto válido a partir de 13 de agosto de 2012 não podem pedir o reassentamento para seus familiares.…”
unclassified